DEVELOPMENT OF THE QUALITIES OF RESPONSIVENESS AND INITIATIVE IN FUTURE TEACHERS - Jamolova Gulbanbegim Muzaffarovna; Hamidova Umida Tilovovna (Web of Journals Publishing, 2025)
In this article, the pedagogical foundations and priorities of the development of suggestive abilities in future teachers, today have the ability to improve the system of training of educators, improve the skills of educators, develop pedagogical skills and abilities. Each pedagogical ability has its own specificity, and it is illuminated that it is necessary for their educator to know and be able to form these abilities in himself. In our country, on the basis of advanced foreign experience, research is being carried out to modernize the content of modern training of young teachers for the system of continuing education, to create a learning environment aimed at creating the necessary conditions that allow students to realize their internal capabilities. In the strategy of Action for the further development of the Republic of Uzbekistan, such priorities as "further improvement of the continuous training system, increase the capabilities of quality training services, continue the policy of training highly qualified personnel in accordance with the modern needs of the labor market" are established.
Keywords: Pedagogical skills, education and development, education, practical skills, continuing education, individual qualities, economic development, educational standards, education and upbringing, scientific and methodological, subjective novelty.